Performance and emission characteristics of micro gas turbine engine fuelled with bioethanol-diesel-biodiesel blends - Saifuddin N.; Refal H.; Kumaran P. (Universiti Malaysia Pahang, 2023)
Biodiesel is receiving increasing attention as an alternative fuel due to the ever-growing demand for energy. However, the inferior physiochemical properties of biodiesel render it incompatible for gas turbine application, which needs to meet the standard requirement of gas turbine fuel accordance to ASTM D2880. In this quest, the biodiesel-diesel- bioethanol blends might be a good option. In this paper, the research work was carried out to study experimentally the performance and exhaust emission characteristics of a 25kW micro gas turbine engine (Capstone Model C30) fuelled with biodiesel-dieselbioethanol blends. The assessment on the improved fuel properties of biodiesel by blending with bio-ethanol had shown more superior atomisation characteristics performance compared to unmodified biodiesel. Moreover, the performance test in the micro gas turbine was limited up to 20% blend of biofuel, which showed improved thermal efficiency during the test. Subsequently, the emission test carried out in this work also showed significant enhancement in emissions, except nitrogen oxides (NOx) which contributed to the higher formation in comparison with the distillate diesel. Finally, B80E20 (80:20 of biodiesel-bioethanol) was proposed to be selected as an ideal blended fuel ratio to be applied in micro gas turbine engine due to its adaptability to replace diesel fuel, while showed better performance and emission properties as compared to the pure petroleum diesel. Universiti Malaysia Pahang Publishing.